2022
DOI: 10.3390/nano12223950
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alkylamines in Tuning the Morphology and Optical Properties of SnS2 Nanoparticles Synthesized by via Facile Thermal Decomposition Approach

Abstract: The present study reported the synthesis of SnS2 nanoparticles by using a thermal decomposition approach using tin chloride and thioacetamide in diphenyl ether at 200 °C over 60 min. SnS2 nanoparticles with novel morphologies were prepared by the use of different alkylamines (namely, octylamine (OCA), dodecylamine (DDA), and oleylamine (OLA)), and their role during the synthesis was explored in detail. The synthesized SnS2 nanostructures were characterized using an array of analytical techniques. The XRD resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Sazanova et al [ 1 ] reported the synthesis and characterization of zinc oxide (ZnO) nanoparticles by plasma-enhanced chemical vapor deposition, establishing that the synthesizing parameters of zinc source temperature and reactor temperature can effectively control the size and morphology of ZnO nanostructures. Gaur and coworkers [ 2 ] synthesized SnS 2 nanoparticles using a thermal decomposition approach and produced novel morphologies (e.g., nanoparticles, nanoplates, and flower-like morphologies assembled from flakes) by using different alkylamines as capping agents. Shao and coworkers [ 3 ] synthesized the Ag@MXene hybrids and studied their nonlinear optical characteristics, making great contributions to the development of ultrathin optoelectronic nanodevices and optical limiters.…”
mentioning
confidence: 99%
“…Sazanova et al [ 1 ] reported the synthesis and characterization of zinc oxide (ZnO) nanoparticles by plasma-enhanced chemical vapor deposition, establishing that the synthesizing parameters of zinc source temperature and reactor temperature can effectively control the size and morphology of ZnO nanostructures. Gaur and coworkers [ 2 ] synthesized SnS 2 nanoparticles using a thermal decomposition approach and produced novel morphologies (e.g., nanoparticles, nanoplates, and flower-like morphologies assembled from flakes) by using different alkylamines as capping agents. Shao and coworkers [ 3 ] synthesized the Ag@MXene hybrids and studied their nonlinear optical characteristics, making great contributions to the development of ultrathin optoelectronic nanodevices and optical limiters.…”
mentioning
confidence: 99%